1992
DOI: 10.1093/cvr/26.12.1172
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in energy substrate use by the heart

Abstract: Marked changes in intermediary metabolism occur during development of the heart. In the fetus, the heart utilises lactate and glucose as its main energy substrates, while in the adult, fatty acids are the main energy substrate. The transition from carbohydrate to fatty acid metabolism is a complex process which involves maturation of mitochondrial processes and dramatic changes in circulating levels of fatty acids and lactate. In addition, developmental changes in the use of energy substrates also involve chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(200 citation statements)
references
References 0 publications
8
184
1
2
Order By: Relevance
“…Possibly, neonatal cardiomyocytes respond differently to changes in glucose concentration than postmitotic adult cardiac cells. This hypothesis is supported by the changes in substrate metabolism that occur during the perinatal period, when cardiomyocytes shift from predominant nonoxidative glucose utilization to predominant fatty acid oxidation (35). Alternatively, the protective effect of glucose may be limited to apoptotic pathways other than the one induced by palmitic acid.…”
Section: Discussionmentioning
confidence: 98%
“…Possibly, neonatal cardiomyocytes respond differently to changes in glucose concentration than postmitotic adult cardiac cells. This hypothesis is supported by the changes in substrate metabolism that occur during the perinatal period, when cardiomyocytes shift from predominant nonoxidative glucose utilization to predominant fatty acid oxidation (35). Alternatively, the protective effect of glucose may be limited to apoptotic pathways other than the one induced by palmitic acid.…”
Section: Discussionmentioning
confidence: 98%
“…We used, in this study, heparin for anti-coagulation and obtained blood samples www.intechopen.com under heprinized state because of two reasons; 1) for preservation of veins and arteries from obstruction in younger children and 2) for our aim of studying myocardial metabolism in patients under critical states as in pediatric intensive care unit or in surgical intervention where many patients were heparinized. In spite of these limitation, this method we applied here is still useful for clinical study on myocardial metabolism (Vánky et al 2006) because data obtained are supposed not far from animal model study (Lopaschuk et al, 1992), computer simulation study and isotopical study in human.…”
Section: Characteristics Of Methodology On Myocardial Energy Metabolimentioning
confidence: 99%
“…The very variable glucose uptake shown in other reports including adults suggested that glucose may not play an important role for myocardial energy supply for children at rest. (Vánky et al 2006,Lopaschuk et al, 1992. It has been demonstrated that adult hypertrophied hearts prefer to oxidize glucose.…”
Section: Myocardial Use Of Lactate and Other Substrates In Non-cyanotmentioning
confidence: 99%
See 1 more Smart Citation
“…Rate pressure product increased with heart rate and was found to relate to myocardial oxygen consumption (r = 0.75), which increased maximally by 47 ± 9% due to increases in coronary blood flow. Phosphocreatine/ATP ratio decreased significantly, and calculated ADP increased between baseline and peak perMajor modifications in myocardial energy metabolism and regulation occur shortly after birth (1,2). ATP production is tightly coupled to utilization in the newborn myocardium as well as the mature myocardium.…”
mentioning
confidence: 99%